Associations Between Female Sex Hormones and Skeletal Muscle Ageing: The Baltimore Longitudinal Study of Aging - Annabel J. Critchlow; Sarah E. Alexander; Danielle S. Hiam; Luigi Ferrucci; David Scott; Séverine Lamon (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background To date, most research investigating the influence of circulating sex hormones on ageing female skeletal muscle has been cross‐sectional and focused only on dichotomised young and old, or pre‐ versus post‐menopausal groups. This excludes an important transitional period from high to low circulating oestrogen. Using secondary data from the Baltimore Longitudinal Study of Aging, this study aimed to investigate cross‐sectional and longitudinal associations between circulating sex hormones and skeletal muscle mass and function across a continuum of ages. Methods Multiple and binomial linear regression was used to map cross‐sectional (n = 319) and longitudinal (n = 83) associations between circulating sex hormones (oestradiol (E2), free oestradiol index (FEI), total (TT) and bioavailable (BioT), testosterone, testosterone/oestradiol ratio (TT/E2)) and skeletal muscle mass and function in healthy females. Cross‐sectional models analysed females across an ageing continuum (24–89 years) and longitudinal associations were tested across 4–6 years of ageing in females over 50 years old. Models were adjusted for age, height, physical activity, comorbidities, ethnicity, and follow‐up time. Results Cross‐sectionally, serum E2 and FEI were positively associated with relative appendicular lean mass (ALM; β = 0.28 and 0.20, respectively, p < 0.05) and thigh muscle percentage (β = 0.19 and 0.15, respectively, p < 0.05). E2 and FEI were negatively associated with total body fat percentage (β = −0.30 and −0.21, respectively, p < 0.05). BioT was positively associated with absolute ALM (β = 0.13, p < 0.05) and total body fat percentage (β = 0.18, p < 0.05). TT was negatively associated with total body fat percentage (β = −0.14, p < 0.05). The TT/E2 ratio was negatively associated with thigh muscle CSA (β = −0.08, p < 0.05) and hamstring strength (β = −0.12, p < 0.05). Across 4–6 years, decreases in E2 and FEI were associated with a decrease in ALM (β = 0.27 and 0.41, respectively, p < 0.05), and a decrease in FEI was associated with a decrease in handgrip strength (β = 0.21, p < 0.05). Decreases in TT and BioT were associated with an increase in total body fat (β = −0.25 for both, p < 0.05) and a decrease in TT was associated with an increase in hamstring specific force (β = −0.11, p < 0.05). Conclusion This study demonstrates novel associations between sex hormone levels and skeletal muscle in females across a wide continuum of ages. We also demonstrate that longitudinal fluctuations in circulating sex hormones must be considered to gain a comprehensive understanding of female muscle ageing.